O potrzebie opracowania metodyki implementacji systemów zarządzania wiedzą - Tabaszewska, Edyta (On the Need of Formulating the Methodology of Implementation the Knowledge Management Systems, 2008)
Knowledge management (KM) currently represents one of the most popular concepts in management which still is not widely enough applied in practice. The reasons for such situation may be attributed to insufficient indications related to strategies of this concept assumptions' implementation in enterprises. The objective of the article is the presentation of basic problems in elaborating formal methodology of knowledge management system implementation. The article presents the study of methodologies available in literature, points to benefits of using and difficulties in preparing a formalized methodology, as well as conditions of KM systems implementation. (original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 34, s. 78-88